Boycott Campaign, Local Pride, and Switching Intention: An Islamic Consumer Ethics Perspective on AMDK Brand Migration Among Generation Z - Muhammad Wandisyah R Hutagalung; Happy Dewani Lubis; Ismail Pulungan; Muaz Muhammad Abdul Rahim (TANSIQ: Jurnal Manajemen dan Bisnis Syariah, 2026)
This study investigates the influence of boycott campaigns and local pride campaigns on switching intention from Aqua to Le Minerale among Generation Z consumers in Padangsidimpuan City, within the framework of Islamic consumer ethics. Rooted in the principle of maslahah (public welfare) and the Islamic concept of purposive consumption, boycott campaigns in Islamic discourse align with the notion of al-muqata'ah — a permissible act of consumer abstention in response to perceived injustice. Meanwhile, local pride campaigns resonate with the Islamic call for community solidarity (ta'awun) and the preference for products that serve local socio-economic welfare. Employing a quantitative associative-causal approach with 100 Generation Z respondents selected through multi-stage sampling, data were collected via Likert-scale questionnaires and analysed using multiple linear regression in SPSS 27. Results indicate that both boycott campaigns (t = 6.168, p < 0.001) and local pride campaigns (t = 3.685, p < 0.001) exert a significant positive effect on switching intention, and both jointly explain 45.2% of its variance (F = 40.083, p < 0.001). These findings suggest that Islamic ethical values embedded in social campaigns effectively shape Muslim consumer behaviour, and that brand transitions among Generation Z are dynamically influenced by socio-religious and psychological motivations rather than product attributes alone.